Analisis Dampak Inflasi dan Angkatan kerja Terhadap Pertumbuhan Ekonomi di Sumatera Utara - Simangunsong, Sixson Roberto (Cattleya Darmaya Fortuna, 2023)
The researcher was motivated to investigate the potential impact of inflation and labor force participation on economic growth in North Sumatra, given that inflation remained relatively stable and the labor force participation rate was moderate., at a mere 37%. In order to determine whether labor force participation and inflation contribute to current economic growth, researchers used secondary data from the Central Statistics Agency. The variables examined in this study are X 1 Inflation The findings of the study indicate that there is no significant relationship between the two factors and the dependent variable, which is economic growth. It is evident that the outcomes of These two factors do not significantly affect variable Y, which is economic growth. For the independent variable x1 inflation, the t statistical test is -0.2653 with a probability of 0.8080 > 0.05, and the likelihood is 0.9671 > 0.05. Partially in agreement with Hastin's findings, inflation has no appreciable impact on economic growth. The data is normally distributed, nevertheless, if we examine the data's normalcy According to Hastin's research, there is a partial lack of major impact of inflation on economic growth. On the other hand, the data is regularly distributed if we examine its normalcy. Although research indicates that inflation and the labor force can still be utilized as indicators of economic growth, their combined effect is rather marginal